READINESS STUDY OF SOUTH JAKARTA CITY AS CREATIVE CITY THAT SUPPORTS THE DEVELOPMENT OF THE FINE ARTS SUBSECTOR - Nathania, Frida
The creative economy is a new economic wave whose presence is felt by both developed and developing countries around the world. Indonesia itself has started making various efforts to develop the creative economy since 2006. DKI Jakarta, which is the center of growth and the Indonesian economy, also needs to accommodate this development need. There is one administrative city from Special Capital District of Jakarta, namely South Jakarta which later proposed itself as a creative city with a focus on developing the fine arts sub-sector. There are various reasons behind this, including South Jakarta which has the most creative actors from other administrative cities/districts as well as the potential for great art development. Seeing this, the Ministry of Tourism and Creative Economy has a big agenda to make Indonesia a Creative City of Fine Arts in Southeast Asia with South Jakarta as the center of its development. A study is needed that looks at the readiness of the City of South Jakarta to answer the agenda and become the first Creative City of Fine Arts in Indonesia. The research was conducted using a qualitative descriptive method to see how the conditions for implementing creative city development using research component from creative city formula formulated by ICCN and the fine arts sub-sector with research component of fine arts competitiveness from the discussion of the national art development plan that was formulated by the Ministry of Tourism and Creative Economy. The results of the analysis show that the development of a creative city of art in South Jakarta already has the minimum prerequisites needed for every creative city in Indonesia. The preparations that have been made by the City of South Jakarta in developing a creative city of fine arts are effective, efficient, sufficient to be able to develop a creative city of fine arts (directly or indirectly), provide equitable benefits for all target groups, and are considered appropriate to be implemented but it's not very responsive that can answer or satisfy all the values/needs of each existing target group. In addition, the ecosystem of the fine arts industry in South Jakarta has been classified as very good which indicates the suitability of the selected fine arts as a sub-sector to be developed in a creative city.